Navigating “Praxis Shock”: Disentangling an Early Career Teacher’s Emotions and Actions in Organizational Socialization Through a Micropolitical Lens - Ngan, Tran Thi (VNU Journal of Foreign Studies, 2021)
In the present research, we seek to study the process of organizational socialization of early career teachers (ECTs) through a micropolitical lens that focuses on the issues of power, control and influence as part of the ECTs’ sense-making of and acting in their job. By means of a case study with a beginning Vietnamese university teacher, we attempt to answer two questions: (1) what sorts of emotions does the ECT experience in her organizational socialization, and in challenging micropolitical situations in particular? (2) what kinds of action does the ECT employ in such situations? The research material consists of three narrative interviews within one academic year. The findings highlight the importance of the micropolitics of the school as an organization and the multiple emotional dimensions that are present when ECTs strive to reconcile the school micropolitics with their own beliefs and values as teachers. Along with that, the research contributes knowledge about how ECTs learn to negotiate challenging micropolitical situations using diverse types of micropolitical actions. Implications are also proposed with regard to teacher training and induction.